Transdural Blood Supply in Cerebral Arteriovenous Malformations: A Systematic Evaluation of Angioarchitecture - Stein, K.-P.; Moenninghoff, C.; Kneist, A.; Sandalcioglu, I.E.; Forsting, M.; Sure, U. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Arterial transdural blood supply is a rare angiographic phenomenon in cerebral AVMs. This study aimed to evaluate angiographic transdural blood supply characteristics and to describe the clinical peculiarities of these lesions.MATERIALS AND METHODS: A prospective AVM data base of 535 patients, enrolled from 1990 to 2016, was analyzed retrospectively. Clinical information was reviewed through patients' medical charts and radiologic studies. Patients with previous AVM treatment were excluded (n = 28).RESULTS: Patients with (n = 32, male/female ratio = 10:22; mean age, 46 ± 15 years; range, 13–75 years) and without transdural blood supply (n = 475, male/female ratio = 260:215; mean age, 40 ± 18 years; range, 2–87 years) did not show significant differences in clinical presentation (age, hemorrhage, seizures, chronic headache). The predominant nidus size in patients with transdural blood supply was ≥30 mm, with significantly more patients with large AVMs (>60 mm, P = .001). To describe the transdural blood supply, we used 3 grades based on the angiographic transdural blood supply proportion and intensity of AVM nidus perfusion (I–III). Fifty-seven percent of patients with chronic headache had a strong and substantial transdural nidus perfusion (III) and a high-flow transdural blood supply.CONCLUSIONS: Cerebral AVMs with transdural blood supply represent a rare and heterogeneous subgroup. Lesions can be graded by quantifying the transdural blood supply of the nidus and by capturing hemodynamic characteristics. The broad spread of angiographic features and comparable clinical patterns of patients with or without transdural blood supply raises questions about the relevance of the transdural blood supply to the natural history risk of an AVM and the intention for treatment.ECAexternal carotid arteryTDBStransdural blood supply